Preoperative and postoperative clinical signatures of postgastrectomy venous thromboembolism in patients with gastric cancer: A retrospective cohort study - Xiu-ping Li; Yun-ying Wang; Yu-shu Sun; Li-jiao Zhang; Xia-ying Zhao; Zhu-qin Liu; Hui-min Jiang; Jing-dan Zha; Xiao-jie Zhang; Jia-ning Yan; Hong-ying Pan (Asian Journal of Surgery, 2023)
Background: This study aimed to identify preoperative and postoperative risk factors of venous thromboembolism (VTE) after gastrectomy in gastric cancer (GC) patients. Methods: 757 GC patients underwent gastrectomy at our institution and 246 patients with elevated postoperative D-dimer levels who received Doppler ultrasonography of lower/upper extremity veins were enrolled. Clinicopathological factors data were collected, and the differences in clinicopathological factors between postoperative VTE (+) and VTE (−) groups were analyzed. Univariate and multivariate logistic regression analyses were performed to identify independent risk factors of postgastrectomy VTE. Results: Of 246 patients with elevated postgastrectomy D-dimer concentrations, 74 patients showed thrombosis in lower/upper extremity veins. Among preoperative factors, age, WBC level, D-dimer concentration, and blood glucose level were significantly higher in the postoperative VTE (+) group. Among the postoperative factors, hemoglobin level was significantly lower in the postoperative VTE (+) group. Among the pathological factors, tumor stage, depth of invasion and TNM classification indicated higher malignancy in the postoperative VTE (+) group. Univariate logistic regression analysis indicated age, preoperative blood glucose level, postoperative hemoglobin level, tumor stage, depth of invasion, and TNM classification as the independent risk factors for postgastrectomy VTE, whereas multivariate logistic regression analysis revealed age and tumor stage as independent risk factors for postgastrectomy VTE. Conclusion: Our study revealed that age, preoperative blood glucose level, postoperative anemia, and tumor malignancy were independent risk factors for GC patients exhibiting postgastrectomy VTE. Therefore, the perioperative monitoring, assessment and management of risk factors are important in achieving better outcomes after gastrectomy.